Law and ethics in population health - Lawrence O. Gostin (Elsevier, 2004)
Abstract This paper proposes an action agenda to assure healthier and safer populations. First, create a strong public health infrastructure with sustainable funding and secure foundations-a well‐trained workforce, modern data systems, rapid disease surveillance, and laboratory capacity. Second, use law as a tool for the public's health-tax and spend to create incentives for health, alter the informational and built environments to reduce risk behaviours, lower socio‐economic disparities to improve health, regulate for the public's welfare, pursue tort litigation to innovate for safety, and deregulate to reduce harm. Third, create a new public health ethic in society that truly values human health-advocate for a renewed commitment to the ideals of community and partnership, and stress citizens' duties to help and protect their fellow human beings.